Pregnancy stress in women at high risk of preeclampsia with their anxiety, depression, self-management capacity: a cross-sectional study - Cong, Xing; Wang, Jinmei; Yang, Liu; Cui, Lingling; Hua, Yurong; Gong, Ping (Frontiers in Psychology, 2025)
IntroductionMany studies suggest that psychological factors are intrinsically connected to the onset of preeclampsia. However, there are no relevant surveys on the psychological situation of this population. The aims of our study were to investigating the causes and prevalence of pregnancy stress in individuals at high risk of preeclampsia; exploring the correlation between pregnancy stress and anxiety, depression, and self-management capacity in this group. Our study provided evidence for the development of effective clinical management strategies and related psychological care for women at high risk of preeclampsia.MethodsA cross-sectional survey was conducted on women at high risk of preeclampsia who came to Jiangnan University Hospital’s obstetrics outpatient clinic for antenatal care. Sociodemographic and obstetric-related characteristics, Pregnancy Stress Rating Scale (PSRS), Self-rating anxiety scale (SAS), Self-rating depression scale (SDS), Self-rating Questionnaire of Healthcare Management for Pregnancy (SQHMP) were included in this study. Data analysis covered descriptive statistics, univariate analysis, Spearman’s rank correlation, and multiple linear regression analysis.ResultsA total of 138 pregnant women at high risk of preeclampsia were enrolled in the study. Univariate analysis showed significant relationships between intergenerational relations (with mothers-in-law), pregnancy intention, and desired mode of delivery among pregnancy stress (p < 0.001). Median (IQR) scores were: PSRS 0.283 (0.133, 0.542), SAS 38.750 (32.500, 45.000), SDS 41.250 (33.750, 50.000), SQHMP 43.000 (35.000, 53.250). The score of Spearman’s rank correlation showed that pregnancy stress was positively correlated with anxiety, depression, and self-management capacity, respectively (r = 0.465, p < 0.001), (r = 0.437, p < 0.001), and (r = 0.585, p < 0.001). Multiple linear regression analysis showed that desired mode of delivery, anxiety, and self-management capacity were the main predictors of pregnancy stress.ConclusionThe findings emphasize the need to focus on pregnancy stress in women at high risk of preeclampsia, especially those have presented higher levels of anxiety, depression, and self-management capacity. Based on these variables, healthcare professionals should increase screening for mental health in pregnant women at high risk of preeclampsia as well as provide additional psychological care.